PENGARUH PEMBELAJARAN RECIPROCAL TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS - Lilik Setiawati (Mat-Edukasia, 2017)
This study aims to describe the understanding of mathematical concepts using reciprocal teaching learning models better than conventional learning on congruence material. This study uses a quantitative approach with the experimental method. The research design used was a posttest control only design with a population of class IX students at SMP Negeri 7 Merangin. The technique of collecting data uses a test with a description problem instrument. Hypothesis testing uses independent sample t-test because data is normally distributed and has a homogeneous variance. From the analysis of the final test data on the experimental class obtained an average of 12.13, while the control class obtained an average of 10.38, the results of the hypothesis test obtained, = 1.709 and = 1.682. Because> then Ha is accepted and Ho is rejected. It can be concluded that understanding mathematical concepts by using reciprocal teaching learning models is better than conventional learning in class IX students of Merangin 7 Middle School. Keywords: Reciprocal Teaching Learning Model, Understanding Mathematical Concepts